Physical Exercise and Bone Density Score of Older Adults Having High Risk of Falls - Ade Irma Rahayu; Arnis Puspitha; Ahmad Dahlan Syam; Hasriyani Hasriyani (Faculty of Nursing, Universitas Hasanuddin, 2016)
Introduction: Decreased Bone Mineral Density (BMD) is considered as a determining factor of injury from falls. Previous study revealed that physical exercise contributes to the changes of fall risk of older adults with leg muscle strength, balance, and BMD as its intervening variable. This study aimed to determine the effect of physical exercise on BMD value among elderly with high risk of fall in Makassar. Method: We used two-group pretest-posttest design. Ten women aged > 60 with high risk of fall were involved using purposive sampling based on inclusion and exclusion criteria. The researchers used exercise guidelines made by Indonesian Ministry of Youth and Sport. BMD was measured on the sole of the feet using Bone Densitometry and interpreted as z-score. Data were processed using SPSS and tested by Paired Sample T-Test and Independent T-Test. Result: Almost half of the elderly had low BMD value that leads to osteopenia. There was no effect of physical exercise to the BMD changes among elderly (p = 0.675 for experiment group) and significant difference for both groups was p = 0.86. However, mean difference showed that experiment group had higher changes of BMD value compared to control group. Conclusion: Physical exercise has no overall treatment effect on bone mineral density in older women with high risk of fall. It is recommended that a longer period of time of physical exercise. Measured BMD using DXA on hip and lumbar spine is also needed for further studies